Identification and characterization of serine protease inhibitors in a parasitic wasp, Pteromalus puparum. Issue 1 (December 2017) - Yang, Lei; Mei, Yaotian; Fang, Qi; Wang, Jiale; Yan, Zhichao; Song, Qisheng; Lin, Zhe; Ye, Gongyin
Abstract Serine protease inhibitors (SPIs) regulate protease-mediated activities by inactivating their cognate proteinases, and are involved in multiple physiological processes. SPIs have been extensively studied in vertebrates and invertebrates; however, little SPI information is available in parasitoids. Herein, we identified 57 SPI genes in total through the genome of a parasitoid wasp, Pteromalus puparum . Gene structure analyses revealed that these SPIs contain 7 SPI domains. Depending on their mode of action, these SPIs can be categorized into serpins, canonical inhibitors and alpha-2-macroglobulins (A2Ms). For serpins and canonical inhibitors, we predicted their putative inhibitory activities to trypsin/chymotrypsin/elastase-like enzymes based on the amino acids in cleaved reactive sites. Sequence alignment and phylogenetic tree indicated that some serpins similar to known functional inhibitory serpins may participate in immune responses. Transcriptome analysis also showed some canonical SPI genes displayed distinct expression patterns in the venom gland and this was confirmed by quantitative real-time PCR (qPCR) analysis, suggesting their specific physiological functions as venom proteins in suppressing host immune responses. The study provides valuable information to clarify the functions of SPIs in digestion, development, reproduction and innate immunity.